Touch in the Helping Professions : Research, Practice and Ethics - Guirguis-Younger, Manal, 1967-; Malette, Judith, 1963-; Rovers, Martin W. (Book collections on Project MUSE., 2017)
Inappropriate touch cases have sparked public outcry and made headlines, but a discussion on the importance and ethics of positive, caring, appropriate touch in the helping professions such as teaching, nursing and counselling is long overdue.